PERGESERAN LEGITIMASI BALIAN DALAM LOCAL INDIGENOUS GOVERNANCE DI DESA HINAS KANAN - Muhammad Rezani; Ferdinan Salim; Fijaini Fijaini (Jurnal Administrasi Publik dan Pembanguan, 2020)
Balian used to be a Customary Institution that organizes all life of the village community in the Meratus Mountains, including managing the village by upholding the local wisdom. Since the New Order, the paradigm of “the state-enters-the village” governs villages through its set of legislation in the governmentality scheme. Behind the shield of will to improve (KAT empowerment) as a media of discursive power (Li, 2007), the government reshape all social order and local indigenous social governance to “obey” to one formal rule. Unconsciously or intentionally, that governmentality has triggered a shift in local indigenous governance from the basis of local wisdom to the basis of modern governance, with the risk of a shift in the legitimacy of Balian’s power vis-à-vis its community. This study is built on Foucault’ theory of governmentality (1982) and Li’s will to improve (2007). The research method used in this study was a qualitative descriptive method by collecting data, in-depth interviews, and participatory observation. The shift led the role and function of the Balian to be no longer the sole holder of local governance with a local wisdom approach. In the current local governance, it is held by the Village Government, the Sub-District Customary and Balian’s Heads. The shifts that also occurred in the community included the shifting of traditional culture in selling rice which was once considered a taboo to be a commonplace thing and the tendency of the community to resolve conflicts with government institutions rather than the customary or Balian’s Heads.